Controllable Synthesis of Carbon Yolk‐Shell Microsphere and Application of Metal Compound–Carbon Yolk‐Shell as Effective Anode Material for Alkali‐Ion Batteries (Small Methods 3/2023). Issue 3 (13th March 2023) - Kim, Yeong Beom; Seo, Hyo Yeong; Kim, Sang‐Hyun; Kim, Tae Ha; Choi, Jae Hyeon; Cho, Jung Sang; Kang, Yun Chan; Park, Gi Dae
Abstract : Back Cover In article number 2201370, Cho, Kang, Park, and co‐workers proposed a novel synthesis strategy for a nanostructured carbon yolk‐shell microsphere that allows for the control of morphology and size of the yolk part for the first time. The prepared carbon yolk‐shell microsphere was utilized as an effective reservoir for ultrafine metal compound nanocrystals. This rational synthesis strategy could be employed to further improve their application potential in various fields.